Independent Personal Services in the Brazilian Double Tax Conventions - Duarte Filho, Paulo César Teixeira (Revista de Direito Tributário Internacional Atual, 2017)
This article tries to critically define the Brazilian policies related to the income from rendering of independent professional activities, present in the Article 14 of the double tax conventions (“DTCs”) signed with several countries. Based on the premises developed along the study, it was possible to structure what would be the text-basis of Article 14 used by the country to negotiate with its partners, main characteristics, possible issues and the consequences in the bilateral relationships. The paperwork was designed, firstly describing how Article 14 is delineated in the main model-conventions, as the OECD’s and the UN’s; subsequently, the Brazilian conventions were submitted to analysis; at the end, the article brings final considerations and a summary of the presentation of Article 14 in the various conventions signed by Brazil.